2017
DOI: 10.1016/j.ihj.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of cardiac autonomic status by heart rate variability between under-treatment normotensive and hypertensive known type 2 diabetics

Abstract: Our findings of HRV suggest that in type 2 diabetics with poor glycaemic and good pressure control, hypertension as a co-existing factor does not make significant difference in cardiac dysautonomia emphasizing residual risk despite antihypertensive treatment and need for early HRV screening, strict glycaemic control and other interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
(40 reference statements)
0
16
2
Order By: Relevance
“…LF/HF ratio denotes sympatho-vagal balance, and an increase signifies sympathetic dominance which could result from either damage to cardiac autonomic nerves by hyperglycemia in T2DM or by the sympathetic overactivity as seen in HTN. Findings of Solanki et al 44 , 45 were in contrast to those of previous studies, where they reported no significant effect of HTN on autonomic function in T2DM. However, they did not include healthy controls or a euglycemic hypertensive group which makes it difficult to compare it with the results of the present study.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…LF/HF ratio denotes sympatho-vagal balance, and an increase signifies sympathetic dominance which could result from either damage to cardiac autonomic nerves by hyperglycemia in T2DM or by the sympathetic overactivity as seen in HTN. Findings of Solanki et al 44 , 45 were in contrast to those of previous studies, where they reported no significant effect of HTN on autonomic function in T2DM. However, they did not include healthy controls or a euglycemic hypertensive group which makes it difficult to compare it with the results of the present study.…”
Section: Discussioncontrasting
confidence: 89%
“…More recently, Istenes et al 14 assessed resting HRV using the frequency domain measures and found an additive effect of HTN on impaired autonomic function in diabetic patients. However, Solanki et al 44 , 45 found non-significant difference in HRV parameters (frequency domain, time domain and non-linear measures) between diabetics with optimal vs. poor BP control. They recorded no difference in the overall HRV except for LF/HF ratio, which was found to be lower in the hypertensive diabetics.…”
Section: Discussionmentioning
confidence: 98%
“…Conveniently, the measurement of HRV is non–intrusive and pain–free [ 19 ]. Although the evaluation of HRV in T2DM has been assessed in several studies, conflicting results have been reported [ 20 22 ]. Moreover, there is no consensus on the decreased levels of HRV parameters in T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…We did not find significant difference between new or old cases and with duration less than or more than 4 years with respect to PWA parameters, in line with our previous studies in diabetics with different cardiovascular parameters. [1223242526] It indicates the importance of presence of disease, early diagnosis, physical activity, and prompt treatment more than further chronicity or glycemic control.…”
Section: Discussionmentioning
confidence: 99%